1993
DOI: 10.1159/000236511
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Localization of Prostaglandin Endoperoxide Synthase (Cyclooxygenase) to Isolated, Purified Fractions of Guinea Pig Peritoneal Macrophage and Line 10 Hepatocarcinoma Cell Lipid Bodies

Abstract: Subcellular fractions of purified cytoplasmic, nonmembrane-bound lipid bodies were prepared from [3H]-arachidonic acid-labeled guinea pig peritoneal macrophages and line 10 hepatocarcinoma cells. These fractions, which contained [3H]-arachidonyl lipids, were shown to be devoid of contaminating cellular membranes by electron microscopy, and to contain prostaglandin endoperoxide (PGH) synthase by postembedding immunogold electron microscopy. These findings support a proposed role for these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 9 publications
1
39
0
2
Order By: Relevance
“…The cellular function of LDs is considered both detrimental as well as protective. The fi rst is illustrated by eicosanoids production from the FFAs released during triglyceride (TG) hydrolysis ( 14 ), whereas the protective effect was hinted at by longer survival under stress of cells that produce TGs ( 15 ). Membrane phospholipids provide the building blocks for stress-induced LD synthesis ( 16 ).…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…The cellular function of LDs is considered both detrimental as well as protective. The fi rst is illustrated by eicosanoids production from the FFAs released during triglyceride (TG) hydrolysis ( 14 ), whereas the protective effect was hinted at by longer survival under stress of cells that produce TGs ( 15 ). Membrane phospholipids provide the building blocks for stress-induced LD synthesis ( 16 ).…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…Lipid bodies serve as sites for localization of esterified arachidonate and eicosanoid-forming enzymes (25,29), and certain leukotrienes mediate some of the effects of PAF in vivo (30 -32). We asked whether the cellular response to oxidized phospholipids required these eicosanoids.…”
Section: Oxidized Phospholipids Induce the Expression Of 5-lipoxygenamentioning
confidence: 99%
“…However, mechanisms that regulate lipid body formation and their functional significance to the cellular biology of the tumor are not known. Recent studies based on lipid body content have shown that lipid bodies, beside their rich lipid content, contain several functionally diverse types of proteins, including adipose differentiation-related protein (ADRP) and caveolin (6)(7)(8)(9), lipid metabolic enzymes and proteins of Rab family (10)(11)(12), eicosanoid-forming enzymes (13,14), and protein kinases, such as phosphoinositide 3-kinase (PI3K), mitogenactivated protein kinase, and protein kinase C (PKC; refs. [15][16][17].…”
Section: Introductionmentioning
confidence: 99%